Decomposição ácida assistida por ultrassom para a determinação de Cu, Fe, Mg e Zn por F AAS em cerâmicas de uso doméstico - Eliézer Quadro Oreste; Alexander Ossanes de Souza; Camila Corrêa Pereira; Mariana Antunes Vieira; Anderson Schwingel Ribeiro (Química Nova)
This paper describes a sample preparation method for domestic ceramics, based on the acid decomposition assisted by ultrasound for further determination of Cu, Fe, Mg and Zn by Flame Atomic Absorption Spectrometry technique. The main optimized conditions were: particle size (25 µm); sample mass (25 mg) and the acid volume (0.5 mL of HNO3 and 0.5 mL of HF). The samples were placed in an ultrasonic bath for 2 hours at 40 ºC. The method was employed for eight commercial samples of domestic ceramic, which showed different concentrations for all analytes investigated, showing the existing variety of raw materials. The method showed good accuracy and precision, attested by the addition and recovery test, with values of 87 to 112% for all analytes and relative standard deviation lower than 3.0%.